Unraveling the New Paradigm of Pancasila Education: Welcoming the Era of Society 5.0 and its Navigation Challenges - Sofyan, Edy; Marlina, Rina; Pandikar, Ernandia; Hendriawan, Erry (ann4publisher@gmail.com, 2024)
The human-centered society of Japan, which pursues system integration to strike a balance between social problem-solving and economic advancement, is the source of the idea of society 5.0. Keeping the digital and physical worlds in balance is crucial. Considering how quickly technology is developing these days, the nation's next generation needs to be raised with the principles of Pancasila. This publication aims to identify the challenges that will arise and the practical strategies that may be used to implement Pancasila education in the Era of Society 5.0. To this end, a literature study and literature review have been conducted. The topic of discussion will be the function and application of Pancasila values. A plan to execute Pancasila education will then be based on this. Early implementation of Pancasila schooling is a viable method in Era Society 5.0. Pancasila education can only be applied in formal educational settings, such as at home, by parents. It need only be taught in schools. Nationalist sentiment can be ingrained in the nation's future generation through Pancasila education from a young age.